Speckle reduction in ultrasound images of atherosclerotic carotid plaque - Loizou, Christos P.; Christodoulou, Christodoulos; Pattichis, Constantinos S.; Istepanian, Robert S H; Pantziaris, Marios; Nicolaides, Andrew N. (My University, 2002)
The objective of this work was to develop six speckle reduction-filtering techniques and evaluate them together with texture analysis in the assessment of 240 ultrasound images of the carotid artery. The de- speckled filters are based on anisotropic diffusion, local statistics with higher moments, and geometric filtering. Results showed that some improvement in class separation (between symptomatic and asymptomatic plaques) of the images was evident after de-speckle filtering.
Keywords: Speckle; Ultrasonic imaging; Filters; Anisotropic magnetoresistance; Image texture analysis; Carotid arteries